Degradation of the main gas pipeline material and mechanisms of its fracture - Maruschak, Pavlo; Danyliuk, Iryna; Prentkovskis, Olegas; Bishchak, Roman; Pylypenko, Andriy; Sorochak, Andriy (Journal of Civil Engineering and Management, 2014)
The effect of the in-service scattered damage in the pipe wall metal is evaluated, and the effect of hydrogen absorbed by metal on the variation of the structure and mechanical properties of the main gas pipeline after a long-term operation is found. The main regularities in the graded nature of the static deformation process and the effect of hydrogenation on the scattered damage and fracture accumulation are found.